Synthesis and Crystal Structure of Three New Quaternary Compounds in the system Cu-Mn-III-Se3 (III = Al, Ga, In) - Gerzon E. Delgado; Jesus A. Flores-Cruz; Pedro Grima-Gallardo; Miguel Quintero; Alvaro Moreno (Materials Research, 2018)
Chalcogenide alloys CuMnAlSe3, CuMnGaSe3 and CuMnInSe3, new members of the semiconductor system I-II-III-VI3, were synthetized and structurally characterized by the Rietveld method using X-ray powder diffraction data. All compounds crystallize in the tetragonal space group P4 2c (Nº 112) with a CuFeInSe3-type structure.